2012
DOI: 10.4236/fns.2012.33044
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Taste Sensitivity and Eating Style in Japanese Female University Students

Abstract: This study investigated the relationship between taste sensitivity, the frequency and the preference for eating foods rich in zinc, dietary habits, and restrained eating among Japanese female undergraduate students. Forty-three subjects between the ages of 20 and 22 participated in this study. After a taste-sensitivity test for sweetness and saltiness the students completed a food list indicating the intake frequency and preference of foods rich in zinc and their eating habits. The students were divided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…However, it is noteworthy that there were a high percentage of people with low sensitivity to sweet and salty tastes in both groups. Other researchers also observed that both healthy people and Crohn's disease patients exhibited low sensitivity to salty and sweet tastes (Bertoli et al, ; Kato & Roth, ; Martin & Bellisle, ), which could be partly explained by their dietary habits (Jayasinghe et al, ; Santos et al, ). Santos et al () found that only 18.0% of Brazilian adolescents preferring sweet taste were able to correctly identify it at refined sugar concentrations of 2.0 and 4.0%, as well as the salty taste of table salt at concentrations of 0.2 and 0.4%.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, it is noteworthy that there were a high percentage of people with low sensitivity to sweet and salty tastes in both groups. Other researchers also observed that both healthy people and Crohn's disease patients exhibited low sensitivity to salty and sweet tastes (Bertoli et al, ; Kato & Roth, ; Martin & Bellisle, ), which could be partly explained by their dietary habits (Jayasinghe et al, ; Santos et al, ). Santos et al () found that only 18.0% of Brazilian adolescents preferring sweet taste were able to correctly identify it at refined sugar concentrations of 2.0 and 4.0%, as well as the salty taste of table salt at concentrations of 0.2 and 0.4%.…”
Section: Discussionmentioning
confidence: 95%
“…Further research is necessary to investigate the influence of folic acid intake on increased sensory sensitivity to sour taste and reduced sensitivity to bitter taste. Earlier studies on healthy people showed a relationship between taste sensitivity and the intake of some micronutrients, for example, the intake of food with high zinc content (Kato & Roth, ; Stewart‐Knox et al, ). Women's higher dietary intake of zinc was associated with their better sensitivity to salty taste (McDaid, Stewart‐Knox, Parr, & Simpson, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies suggested that the ability to perceive sweet taste influences the blood glucose levels by altering the amount of sugar consumed and dietary and snacking habits. Individuals with lower sensitivity to sweet taste tend to have greater dietary and sugar intake and thus can be at risk of long-term health outcomes, such as obesity, because they need to consume more sugar to have the same taste sensation than those who are more sensitive [11,12]. Furthermore, previous studies found that there was a significant increase of the mean sweet International Journal of Dentistry taste threshold in the diabetic group compared to the normoglycemic group [13,14].…”
Section: Discussionmentioning
confidence: 99%